Touchdown Kid - Green, Tim, 1963- (Harper, an imprint of HarperCollinsPublishers, 2017)
Sharing a love of football and life in a rough neighborhood, Cory and his best friend, Liam, are tested when Liam sustains an injury that costs him a football scholarship and Cory is offered his friend's scholarship and must learn how to fit in with his privileged new classmates.